A Novel Cost-Effective Technique for Speedy Resolution of Infantile Umbilical Hernia: Ammannaya's Technique. (10th September 2019) - Ammannaya, Ganesh Kumar K.; Sripad, Ninada
Abstract : Umbilical hernia in the infant is common and resolves in majority of the cases by 6 years of age. Observation till this age and surgery in the event of persistence are the widely followed management strategies. Trusses, taping, and adhesive strapping have been tried to achieve speedy resolution with variable success and a significant incidence of skin complications. We present a novel, simple, easily reproducible, and highly cost-effective technique to achieve complete resolution of infantile umbilical hernia in a span of 8 weeks, with no skin complications.